2013
DOI: 10.5296/jse.v3i2.3424
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Knowledge and Use of Assistive Technology for Students with Special Educational Needs

Abstract: Students with disabilities face many challenges in learning and assistive technology can be a potential aid for compensating for their educational needs. The purpose of this research was to gather information about assistive technology knowledge and skills among teachers. Data were collected from one hundred and twenty-seven participants via a self reporting questionnaire. Interviews were also used with three participants to gather data of greater breadth and depth to the analysis of the data gathered from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 21 publications
3
41
1
5
Order By: Relevance
“…Research revealed a lack of AT training within initial teacher education programs in general, resulting in a lack of knowledge around AT (Alkahtani, 2013;Laarhoven, Munk, Chandler, Zurita, & Lynch, 2012;Morrison, 2007). Often times, AT training is only briefly covered in elective special education courses, thus, limiting pre-service teachers' exposure to, and knowledge of, devices and their use within the classroom (Morrison, 2007).…”
Section: Prevalent Barriersmentioning
confidence: 99%
See 4 more Smart Citations
“…Research revealed a lack of AT training within initial teacher education programs in general, resulting in a lack of knowledge around AT (Alkahtani, 2013;Laarhoven, Munk, Chandler, Zurita, & Lynch, 2012;Morrison, 2007). Often times, AT training is only briefly covered in elective special education courses, thus, limiting pre-service teachers' exposure to, and knowledge of, devices and their use within the classroom (Morrison, 2007).…”
Section: Prevalent Barriersmentioning
confidence: 99%
“…One open-ended question asked participants who perceived that their students were not using AT software within the classroom properly (or were unsure) to expand on their response. In addition, three questions were replicated from Alkahtani's (2013) research that asked participants to estimate the amount of training they had received pertaining specifically to AT (i.e., workshops, in-service, and formal college or university courses in which AT was covered in detail).…”
Section: Survey Designmentioning
confidence: 99%
See 3 more Smart Citations